PENGEMBANGAN PERANGKAT PEMBELAJARAN MENGGUNAKAN DEDUKTIF INDUKTIF BERBANTUAN GEOGEBRA DALAM MENINGKATK KEMAMPUAN BERPIKIR KREATIF SISWA PADA MASA PANDEMI - Sugandi, Asep Ikin; Sofyan, Deddy; Maesaroh, Siti (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2021)
The purpose of this study was to produce learning tools using geogebra-assisted inductive deductive approaches that were valid, practical and effective in improving students' creative thinking abilities. This research method is a development method. This study develops learning tools that include a Learning Implementation Plan (RPP) and Student Worksheets (LKS) using the Plomp model which consists of three stages, namely the initial investigation phase, the development phase and the evaluation phase. Data processing techniques consisted of validity analysis using validation sheets, practicality analysis techniques using questionnaires from students and teachers and the last analysis of effectiveness using questions about the ability to think mathematically creatively. The results showed that the results of the validation of the learning tools indicated that the learning devices were feasible with a very valid category, while the results of the trials showed that the learning tools developed were very practical and very effective.